Islamic understanding of information society : interview with muslim scholars - Ghanbari, Abbas; Abu Hassan, Musa (Universiti Putra Malaysia Press, 2011)
The chapters presented in this book deal with the various aspect of information society from the perspective of Muslims communication scholars. Information society is the term most often used to describe the historical transformation that the world is witnessing from the end of 20th to the early 21st century. In different disciplines, a lot of scholars are particularly diligent in investigating the nature, aspect and components and the consequences of this new multidimensional phenomenon. Communication study as a field is no exception from this matter. Especially as it is said that information society is a consequence of communication revolution and almost come to be accepted as an objective description of our time and the type of society which is emerging.The importance of this book is because of its contribution to the context of knowledge, especially from Islamic perspective. This is because, although much has been written about information society over the past forty years, little attempts have been made to put forth an Islamic understanding of this phenomenon especially with regard to the Current Muslim World’s situation. Thus, this book contains very informative interview with 10 noted Muslim Communication scholars about this phenomenon and try to highlight subnet and components of information society that has received little attention in the literature, especially with regard to Muslim nation’s structures.